2017
DOI: 10.1021/acs.jpclett.6b02759
|View full text |Cite
|
Sign up to set email alerts
|

All-Atom Molecular Dynamics Simulations of Entire Virus Capsid Reveal the Role of Ion Distribution in Capsid’s Stability

Abstract: Present experimental methods do not have sufficient resolution to investigate all processes in virus particles at atomistic details. We report the results of molecular dynamics simulations and analyze the connection between the number of ions inside an empty capsid of PCV2 virus and its stability. We compare the crystallographic structures of the capsids with unresolved N-termini and without them in realistic conditions (room temperature and aqueous solution) and show that the structure is preserved. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…The results of the publication allowed to conclude that the correct assembly of the virus proceeds in the presence of RNA, while empty capsids are not formed. We have also observed this behaviour of capsid deformation for a different virus PCV2 [5] when the genome is absent inside the capsid. We have shown that such instability is caused by incorrect distribution of ions on the capsid's surfaces (inside and outside).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…The results of the publication allowed to conclude that the correct assembly of the virus proceeds in the presence of RNA, while empty capsids are not formed. We have also observed this behaviour of capsid deformation for a different virus PCV2 [5] when the genome is absent inside the capsid. We have shown that such instability is caused by incorrect distribution of ions on the capsid's surfaces (inside and outside).…”
supporting
confidence: 61%
“…A set of such viruses of various sizes can serve as convenient models for tuning and validating MD simulations. Figure 1 Cross-cut through the all-atom model of PCV2 capsid without genome immersed in a simulation box filled with explicit water [5] This perspective is devoted to all-atom MD simulations of whole viruses or their complete capsids. Importantly, we consider only works on atomistic modelling, excluding (much more numerous) publications on coarse grained simulations of viruses.…”
mentioning
confidence: 99%
“…Both structures are stable in physiological environments and they have good agreement with experimental data. We have demonstrated in our previous paper [18] the small value of the RMSD for the structures compared to the Xray structure.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…The radial profile in the interior of the capsid is quite strong and likely to arise from the PCV2 N-terminus (amino acids 1-36) and additional material. We assumed that cellular RNA was present in the capsid to stabilize the positive charge of the capsid interior (66). To calculate the amount of RNA present in the PCV2 capsid, we used the asymmetric image reconstruction of MS2 (EMD-8397) as a standard -as the ssRNA genome of MS2 is resolved in this image reconstruction (22).…”
Section: Methodsmentioning
confidence: 99%